Influence of parents involvement towards efficiency of education system in secondary school at Pengkalan Chepa with regards to education delivery - Nurul Hanis Zulkifli (2018)
After Malaysia get independence,Malaysia has come out with its own education system which it has been created in a way that can fulfil the needs and satisfaction from its all multiracial citizens.Malaysia decided to create in that way because of it want to make sure that everyone lives peacefully and harmoniously.Education system in Malaysia is manage by Ministry of Education (MOE).MOE has come out with education system that involves pre-school education,primary education,secondary education,post-secondary education and tertiary education.Basically,every level of education in Malaysia will always having parent who make an involvement with the purpose of to make sure their children get good achievement at school.Parent’s involvement in education system can give positive effects when the way they involve is in appropriate way.But somehow,it happened to turn out with negative effect when parent’s involvement was not in a good way.Since Malaysia want to create individuals who have knowledge and competent,Malaysia has come out with different way of education delivery which this also help teacher in teaching and learning process at school.It was good to have changes in education delivery but when there were too much changes,it also can cause teacher and student facing struggle to adapt with it.The combination of parent’s involvement in education system and the changes that occurred in education delivery was leads to give effect on teaching and learning process,and also on student’s achievement.